Pengaruh Sapta Produksi Terhadap Usaha Penggemukan Ternak Sapi Di Serdang Bedagai - Fitri Amelia Sihaloho; Juwendi Prayoga; Azrin Azrin; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the effect of sapta production on cattle fattening in Serdang Bedagai. With the increasing demand for cattle in the local market, it is important to understand the factors that influence the productivity of cattle farming. The method used in this study is a quantitative survey, with data collection through questionnaires distributed to cattle farmers in cattle fattening businesses in Serdang Bedagai. Production variables included production cost, feed amount, maintenance, and yield per period. Analysis was conducted to determine the relationship between production variables and farmers' income. The results of the study are expected to provide insight into the dominant factors affecting the production and income of cattle farmers. The findings provide insight for farmers on the importance of production management to increase profits and business sustainability. This study is expected to serve as a basis for the development of more effective production strategies in the cattle farming sector in Serdang Bedagai.